2021
DOI: 10.1519/jsc.0000000000002992
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Training Practices of Sprint Coaches

Abstract: This study describes the results of a survey of resistance training practices of sprint coaches. This study investigated why sprint coaches prescribe resistance training to their athletes, what exercises they select, and what factors are involved with their selection.Forty-one of 73 (56%) sprint coaches with mean 6 SD coaching experience of 8.4 6 6.4 years were included in this study. Coaches completed an online questionnaire consisting of 5 sections: (a) informed consent, (b) coach background information, (c)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(51 citation statements)
references
References 42 publications
2
48
0
1
Order By: Relevance
“…Combined methods training includes both specific sprint training (primary and or secondary methods) and tertiary methods. Researchers, elite coaches, track and field sprinting coaches and team sports strength and conditioning coaches have suggested utilising an integrated approach utilising a combination of specific and non-specific methods is likely to be the most effective way to develop speed [16,43,204,217,[253][254][255]. Elite coaches suggest a combined training approach using non-specific strength training or developing "gym strength" (e.g., heavy back squats) in conjunction with resisted sport-specific actions (e.g., resisted sprinting with sleds) would increase the chances of positive transfer [256].…”
Section: Combined Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Combined methods training includes both specific sprint training (primary and or secondary methods) and tertiary methods. Researchers, elite coaches, track and field sprinting coaches and team sports strength and conditioning coaches have suggested utilising an integrated approach utilising a combination of specific and non-specific methods is likely to be the most effective way to develop speed [16,43,204,217,[253][254][255]. Elite coaches suggest a combined training approach using non-specific strength training or developing "gym strength" (e.g., heavy back squats) in conjunction with resisted sport-specific actions (e.g., resisted sprinting with sleds) would increase the chances of positive transfer [256].…”
Section: Combined Methodsmentioning
confidence: 99%
“…Research has identified researchers, elite coaches, track and field sprinting coaches and team sport strength and conditioning coaches have suggested utilising an integrated approach utilising a combination of specific and nonspecific training performed individually in separate sessions or combinations (e.g., complex or contrast sets) to develop multiple physical qualities and skills simultaneously [16,43,204,217,[253][254][255]. Therefore, further research would be better suited to manipulating the combinations, sequencing and loading parameters of combined specific and non-specific methods to enhance sprint performance longitudinally.…”
Section: Future Research Directionsmentioning
confidence: 99%
“…Combined methods training includes both specific sprint training (primary and or secondary methods) and tertiary methods, recommended by researchers and sprint and football code practitioners to develop sprint performance [24,32,133,[192][193][194]. This combination of both training methods enables practitioners to provide stimuli to develop both mechanical efficiency and the maximal physical capabilities of the lower limb concurrently [110,169,170,195].…”
Section: Combined Methodsmentioning
confidence: 99%
“…Open-ended response questions were assessed using thematic analysis [18], with the following six-stage process: (a) familiarization with the data; (b) generating initial codes; (c) searching for themes; (d) reviewing themes; (e) defining and naming themes; and (f) producing the report. This method of thematic analysis has been previously used in studies surveying S&C coaches [15][16][17]19,20]. Thereafter, overarching clear and identifiably distinct themes, representing the main ideas or patterns emerging from the raw data were generated for each question.…”
Section: Statistical Analysesmentioning
confidence: 99%